An Oilfield Ecological Risk Assessment System Integrating OERAM and GIS - Y.C. Xiu; W.B. Liu; B. Liu; H.X. Li (Chemical Engineering Transactions, 2015)
The oilfield ecological risk assessment model (OERAM) analyzes the effects of the oil pollutants on ecological system. In this paper, according to oilfield characteristics and ecological risk assessment receptor expose effect assessment, a modified oilfield ecological risk assessment model structure is established which referencing the relationship between ecological receptor exposure ways and ecological effect. Comparing the current ecological risk assessment methods, the joint probability evaluation is selected to establish oilfield ecological risk assessment model. Finally, the oil ecological risk assessment system based on geographic information system and geo-database technology is developed integrating the modified oilfield ecological risk assessment model. This system realizes spatial information analysis, ecological risk assessment and results visualization functions. Through the application in Shengli Oilfield, the comprehensive assessment result of oilfield risk could provide decision-making basis for the oilfield environment management.